Introduction: Literature, Power, and the Making of Alternative Knowledges - Maria Luisa Torres Reyes (POETIKA, 2026)
Literature occupies a distinctive position among cultural forms because it does not merely represent the world; it also participates in the production of social meanings through which communities understand history, identity, power, and belonging. Across different historical periods and geographical contexts, literary narratives have functioned as sites where dominant values are reproduced, contested, transformed, and reimagined. They provide frameworks for interpreting collective experiences, negotiating cultural differences, and articulating alternative visions of social life. The essays gathered in this special section demonstrate the enduring significance of literature as a medium through which competing understandings of the past and present are constructed and challenged. Spanning diverse temporal, linguistic, and cultural contexts—from South and Southeast Asian adaptations of Sanskrit epic traditions to contemporary Indonesian children's literature, from eighteenth-century British imperial fiction to contemporary Palestinian resistance literature—the contributions examine how literary texts